(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Current assets are resources that continuously participate in the day-to-day operations of an enterprise and are typically expected to be converted into cash within one year or one operating cycle. They include cash, short-term financial investments, receivables, inventories, finished goods, and other working assets. These assets ensure the continuity of production, trade, and service processes within the enterprise. Therefore, the accurate representation of current assets in accounting records and the establishment of effective control over them are essential prerequisites for maintaining financial stability.